1997
DOI: 10.1074/jbc.272.39.24183
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase-dependent Activation of Insulin Receptor Substrate 1 in Response to Interleukin-4, Oncostatin M, and the Interferons

Abstract: In addition to a role in response to insulin and insulinlike growth factors, insulin receptor substrate 1 (IRS-1) is phosphorylated in response to IL-4, the interferons (IFNs) and oncostatin M (OSM). Here mutant cell lines lacking JAK1, JAK2, or Tyk2 were used to determine the role(s) of the Janus kinase (JAK) family of protein-tyrosine kinases in IRS-1 phophorylation. 32D cells, which do not express IRS proteins, were analyzed for any requirement for these proteins in response to the IFNs. For the mutant huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 60 publications
2
88
0
Order By: Relevance
“…For example, JAK1 activated by either IL-4, IFN-␣, IL-10, or Oncostatin-M activates the p85 subunit of PI3K through tyrosine phosphorylation of the IRS-1 docking molecule (23,24). In this study, IL-10 stimulation of monocytic cells induced the activation of the survival enzyme, Akt-1, the signaling molecule downstream of PI3K.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, JAK1 activated by either IL-4, IFN-␣, IL-10, or Oncostatin-M activates the p85 subunit of PI3K through tyrosine phosphorylation of the IRS-1 docking molecule (23,24). In this study, IL-10 stimulation of monocytic cells induced the activation of the survival enzyme, Akt-1, the signaling molecule downstream of PI3K.…”
Section: Discussionmentioning
confidence: 81%
“…For example, IL-10 induced the activation of PI3K (22,23) possibly through JAK-1 activation. There is evidence to suggest that JAK1 phosphorylates the insulin receptor substrate-1 (IRS-1) docking molecule following interaction of IL-2, IL-4, IL-10, and IFN-␣ with their corresponding receptors (23,24). Subsequently, tyrosine-phosphorylated IRS-1 proteins may recruit the regulatory p85 subunit of PI3K to the plasma membrane through phospho-tyrosine-SH2 domain interactions (25).…”
Section: Stat-1 Mediates the Stimulatory Effect Of Il-10 On Cd14 Exprmentioning
confidence: 99%
“…However, as it has been demonstrated that phosphorylation of tyrosine residues in the IFNaR1 intracellular domain is not required for Stat3 activation (43), other Stat3 docking sites, apart from the IRTAM sequence and not necessarily containing tyrosine residues, may exist on the IFNaR1 intracellular domain. In addition, phosphatidylinositol 3Ј-kinase activation may also be regulated by insulin receptor substrate-1 (IRS-1) for which activation via Tyk2 and JAK1 has been described (54). Although association of MAP kinase (ERK2) with the IFNaR1 subunit has been reported (55), caution must be taken when linking this pathway to antiviral activity since inhibition of mitogen-activated protein/extracellular signal-regulated kinase kinase and mitogen-activated protein kinase activation had no effect on the antiviral activity of IFN␣ (56).…”
Section: Discussionmentioning
confidence: 99%
“…IRS-1/2 can be recruited to Tyr-495 (Y1) of IL-4R␣ after IL-4 stimulation and is subsequently tyrosine phosphorylated (6). Although it has been reported that Jak1 is essential for the cytokine-mediated activation of IRS-1 in fibroblast cells (13)(14)(15), whether IRS is a direct substrate of Jak1 remains unclear.…”
Section: Fes Mediates the Il-4 Activation Of Insulin Receptor Substramentioning
confidence: 99%